ANALISIS OPTIMALISASI PENGELOLAAN ASET PEMERINTAH KOTA PEKANBARU - Fahrial Fahrial; Sugito Hadi (DINAMIKA PERTANIAN, 2019)
ABSTRACT This research aims to identify and inventory the assets, including form, size, physical, and legal, to know the market value (economic benefits) of the Pekanbaru city, to find out the value of the asset adjusted to its allocation or not, and to know the assets that are required to be optimized. The analysis of the drafting of optimization assets in Pekanbaru City is based on the performance, capacity, quality, and quantity of available assets. The research was carried out at the Pasar Sukaramai area, Jenderal Sudirman Street, Ahmad Yani street, Karet street, and Juanda street of Pekanbaru city. The research locations were selected purposively which are the potential area in Pekanbaru City. Analysis of land use optimization that is the Government’s asset of Pekanbaru City used qualitative and quantitative approaches. A qualitative approach was used to analyze the characteristics of land assets and the surrounding area. The analysis method used in this study was a qualitative analysis that was done inductively. The analysis data was done using the highest and best use analysis (HBU) by analyzing the physical feasibility, regulatory eligibility, financial feasibility, and maximum productivity. The analysis results that are based on identification were obtained: a) there is a need for the firmness of the Pekanbaru City Government in terms of enforcing regulations relating to HPL or issuance of regulations related to HPL for making clear regulations, b. The present retribution has been not optimal yet, so the Regional Original Revenue (PAD) does not increase significantly, and c. Determination of the Land Value Zone (ZNT) consistently by following the market price is extremely required referring to the collaboration in determining the value of the percentage of land ownership.